Indicadores de gestión Kpi’s en una empresa exportadora de rosas de la provincia de Cotopaxi - Chachalo Iza, Christian Israel (2022)
The objective of this project is to measure KPI's, before and after quarantine, in a rose exporting company in the province of Cotopaxi-Ecuador. The name of the company has been withheld at the request of the interested party through a confidentiality agreement. To develop the research, a questionnaire with 34 questions was carried out that allowed the construction of 13 KPIs proposed by Camí, (2012). In this sense, the research was descriptive and quantitative. The data collected corresponds to the period October 2019-March 2020 and October 2020-March 2021. Once the indicators for both periods were calculated, the variation between them was analyzed to estimate whether the company had improved or deteriorated in the area of quarantine management. The results show that the company has improved in 8 KPI's and has deteriorated in 5. Within the first group are: quality claims; absenteeism hours; turnover due to dismissal; customer loyalty; unit gross margin; customer satisfaction; average productivity and efficiency in dealing with claims, while in the second group are: performance; daily working hours; sales profits; turnover due to resignation and turnover due to dismissal. Finally, it is concluded that the company has improved mainly in aspects related to external activities, while it has deteriorated in internal activities.